Micro/meso-scale damage analysis of recycled aggregate concrete mixed with glazed hollow beads after high temperatures based on 2D CT images. (15th February 2023) - Miao, Yanchun; Lei, Chuang; Zhang, Yu; Selyutina, Nina; Smirnov, Ivan; Ma, Gang; Liu, Yuanzhen; Lu, Zeyu
Highlights: The image segmentation method was used to obtain the extraction images of concrete pores and cracks. GHB can effectively optimize the internal pore and crack characteristics of concrete under high temperatures. RCA can aggravates internal damage degradation of concrete under high temperatures. The correlation feature between strength, micro/ meso -scale damage and temperature was obtained. Abstract: Fire occurrence may result in significant micro/meso-scale damage inside the concrete structure, including coarsening of pores and evolution of cracks. Such micro/meso-scale damage greatly impacts the load-bearing capacity and durability of the concrete structure. The lightweight, high-strength, internally porous, and highly thermally stable glazed hollow beads (GHB) may alleviate the cracking around the pores boundary and the mortar matrix due to their special pressure release effect, thus improving the fire resistance of concrete. In order to further investigate the reinforcing mechanism of GHB to the fire resistance of concrete, the CT scanning tests on recycled aggregate concrete mixed with glazed hollow beads (RATIC) before and after the high-temperature exposure were carried out in this paper. Firstly, the image segmentation method was used to obtain the extraction images of concrete pores and cracks. Then, the evolution trends of the porosity, average pore diameter, crack fraction, crack density, and average crack width were analyzed, and the correlation of these parameters with the residual compressive strength was discussed. Finally, a thermal damage model of RATIC considering the influence of micro/meso-scale damage and temperature was developed. The results showed that the recycled coarse aggregate (RCA) addition aggravates the evolution of the pores and cracks characteristics, while the GHB incorporation can alleviate this phenomenon to a certain extent and improve the high-temperature deterioration resistance of concrete. In addition, the proposed thermal damage model of RATIC has good applicability.